If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-4 + -12y) + y = -123 (-4 * 2 + -12y * 2) + y = -123 (-8 + -24y) + y = -123 Combine like terms: -24y + y = -23y -8 + -23y = -123 Solving -8 + -23y = -123 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -23y = -123 + 8 Combine like terms: -8 + 8 = 0 0 + -23y = -123 + 8 -23y = -123 + 8 Combine like terms: -123 + 8 = -115 -23y = -115 Divide each side by '-23'. y = 5 Simplifying y = 5
| 8x+6+5x=-21 | | (y-4)(y+4)= | | -15x=-4x | | 2x+6+1x+8=20 | | x+.1236x=500 | | 5x^9y^7+10x^7y^6+25xy= | | -156=12x+6(x+4) | | x+(.22)=150 | | 7x^6-20x^4+19x^3= | | 7+4(2a+1)=-13 | | 12(n-6)=-132 | | .666666x=400 | | .22+x=150 | | 2x^2-28x-30= | | 2+3r=-6r+8r | | f(3)+f(-3)=-x^2-4x+5 | | 7e^5x=10 | | 7-y=4x | | 27=-9(p-4) | | 1.66666y=400 | | (2x+5)+8=4 | | 5(x)-8=48 | | 6n+6n=4n+16 | | E^35t=10 | | 3x-12-4x+12=x+3-x+2 | | -14k+2k-2k=1-13k | | f(-3)=-x^2-4x+5 | | 3x-1=4x+x | | 3x^2-70x+300=0 | | 3x+1=13x+8 | | 2n+3+7n=-24 | | 10y+3=20y-17 |